The health profile of professional soccer players: Future opportunities for injury prevention - Volpi, P.; Taioli, E. (The Journal of Strength and Conditioning Research, 2012)
Injuries are a major adverse event during a soccer player's career; they require medical and surgical treatment and rehabilitation and thus may interrupt the player's activity, often with severe physical and psychological sequel. Specialists have tried to identify the risk factors for injuries, in an attempt to discover predictors that could be prevented and or eliminated before the injury occurs, but the results are scarce. This article reviews the epidemiology of the frequency and occurrence of injuries in Italian soccer players, reports a list of preventable risk factors that are associated with injuries, and identifies preventable risk factors. We have identified personal factors (age, previous traumatic events, physical and biological characteristics of the player, life style habits such as smoking, alcohol, and diet, changes in physical-athletic aspects of the players, such as increased muscle strength, and use of medications) as possible risk factors for injuries. However, environmental factors such as changes in training techniques, field composition, and shoes structure may also have a major influence. This summary indicates that appropriate preventive measures can be undertaken to prevent injuries in professional soccer players. Professionals who are in close contacts with the players should be informed of the predictors of injuries and should be trained to intervene and plan appropriate preventive measures.